The relationship between Malaysia stock market and East Asia stock market / Norfaziela Nordin - Nordin, Norfaziela (Faculty of Business and Management, 2015)
The aim of this study is to investigate the relationship between Korea Stock Exchange KOSPI Index, Tokyo Stock Exchange Tokyo Price Index, Shanghai Stock Exchange Composite Index to the FTSE Bursa Malaysia KLCI Index. The study used Unit Root Test, Normality Test, Simple Linear Regression and Multiple Linear Regression in order to find the relationship among those markets. The daily closing price of stock indices is collected from 4th January 2010 until 30th December 2014. From the result, it reveals that all these stock indices have a significant positive relationship towards FTSE Bursa Malaysia KLCI Index. It means that there are inter dependencies among this East Asia stock market index. These results further our understanding of the relationship between the stock market in East Asia and should be useful for regulator, investor and speculator.